Prevalence and initial diagnostic evaluation of smoking in adolescents from Moa, Holguín - Alexander Torres Molina (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Foundation: smoking in adolescence constitutes a global public health problem, is being considered the main preventable cause of illness and premature death. Objective: to describe smoking behavior in adolescents. Methods: cross-sectional study, carried out from September to December 2022. From a universe of 1,561 adolescents aged 15-19, a sample of 1,444 (92.50%) was selected through deliberate sampling. The study variables: age, sex, smoker, ex-smoker, age of initiation, years of smoking, number of cigarettes consumed per day, smoking load, dependence and motivation. Results: the prevalence of smoking was 17.94%. 0.83% of adolescents expressed having quit the habit (ex-smokers). 55.98% were between 17-18 years of age, and 77.61% were male. 64.86% started smoking between 12 and 14 years old, 52.51% had been smoking for 1-2 years; while 59.85% consumed between 6-10 cigarettes a day. The smoking burden received by 44.34% was 0.25-0.50. 57.08% declared low physical dependence, and 81.13% reported low motivation. Conclusions: the prevalence of smoking in Moa adolescents was similar to that reported by other investigations. It is worrying that more than half of the population studied consumes cigarettes from the age of 12-14, and that, despite showing low levels of dependence; they do not feel motivated to abandon this bad habit.